Aerogel composite material and preparation method thereof
By using silica aerogel, sunscreen and phase change heat storage materials in aerogel composite materials, and using sol pressurization and pressure continuous feed rapid mixing technology, the thickness tolerance of aerogel composites is difficult to control. and the problem of insufficient insulation performance achieves higher thickness consistency and surface quality, reducing production costs and material waste.
Patent Information
- Application Number
- CN202411305452.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-02-07
AI Technical Summary
During the leveling and cutting process, existing aerogel composites have problems such as difficulty in controlling thickness tolerance, insufficient thermal insulation performance, high cost and waste of materials.
Aerogel composite material and its preparation method are adopted, including a matrix material and an aerogel material on its outer surface or inside. The aerogel material is composed of silica aerogel, a light shielding agent and a phase change heat storage material . Through sol pressurization, polycondensation material pressurization and pressure continuous feed rapid mixing technology, rapid immersion and thickness setting of catalytic sol can be achieved, the leveling and cutting steps are reduced, and thickness consistency and surface quality are improved.
Improves thickness consistency and surface quality of aerogel composites, reduces material waste and production costs, and enhances the management of thermal insulation performance and thermal runaway risk.
Smart Images

Figure CN119390423A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aerogel composite material preparation, and in particular to an aerogel composite material and a preparation method thereof. Background Art
[0002] In recent years, aerogel is a three-dimensional nanoporous structure material prepared by the sol-gel method and special drying method. It has the characteristics of extremely high porosity, large specific surface area, extremely low density and thermal conductivity, and has extremely broad application prospects in the fields of thermal insulation. However, aerogel has problems such as low strength and high brittleness, making it difficult to use directly. The current mainstream method is to compound silica aerogel with a fiber substrate to obtain an aerogel composite felt insulation material with a certain degree of flexibility.
[0003] Aerogel thermal insulation composite materials have been applied in the fields of new energy electric vehicle power batteries, etc., and are usually used in the form of sheets for thermal insulation between power battery cells. The thickness consistency of aerogel composite materials is high and the tolerance range is narrow. Therefore, the aerogel composite thermal insulation material prepared with roll-type fiber substrate composite aerogel needs to be leveled and cut before being applied to power batteries. At present, during the leveling process, the aerogel fiber composite sheet is usually subjected to a compression deformation of more than 20%, and the aerogel body can produce a large elastic deformation. After the pressure is released, elastic recovery will occur, resulting in the thickness tolerance being difficult to control and the yield rate being low; on the other hand, excessive compression will also destroy the integrity of the three-dimensional nanostructure of the aerogel body, resulting in insufficient elasticity of the compressed aerogel and reduced thermal insulation performance; furthermore, due to the implementation of the compression and leveling process, it is time-consuming, energy-consuming, and labor-intensive, resulting in increased costs. In addition, a large amount of scraps are easily generated during the cutting process, resulting in waste of aerogel composite materials. During the cutting process, the aerogel powder in the aerogel composite material will fall off to varying degrees. The fallen aerogel powder will cause dust pollution in the processing environment due to its small particle size and light weight.
[0004] Therefore, there is still a need to improve the existing production process of sheet-type aerogel composite materials to improve the thickness consistency or surface quality of the sheet-type aerogel composite materials and reduce material waste. Summary of the invention
[0005] In view of this, the present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides an aerogel composite material and a preparation method thereof, which can improve the thickness consistency of the aerogel composite material, improve the surface quality of the composite material, and reduce material waste.
[0006] In order to solve the above technical problems, this application is implemented as follows:
[0007] According to one aspect of the present application, an embodiment of the present application provides an aerogel composite material, wherein the aerogel composite material comprises:
[0008] Base material; and
[0009] an aerogel material on the outer surface of the matrix material and / or immersed in the matrix material;
[0010] The aerogel material includes silica aerogel, a sunscreen and a phase change heat storage material.
[0011] In addition, the aerogel composite material according to the present application may also have the following additional technical features:
[0012] In some embodiments, the sunscreen includes at least one of titanium dioxide, silicon carbide, zirconium oxide, yttrium oxide, carbon black, potassium titanate whiskers, magnesium hydroxide, aluminum hydroxide, vermiculite or calcium carbonate.
[0013] In some embodiments, the phase change heat storage material includes at least one of an inorganic phase change heat storage material, an organic phase change heat storage material, and a composite phase change heat storage material.
[0014] In some embodiments, the mass percentage of the sunscreen in the aerogel material is 30% to 160%.
[0015] In some embodiments, the mass proportion of the phase change heat storage material in the aerogel material is 0% to 50%.
[0016] In some of the embodiments, the matrix material includes fiber felt and / or foam material.
[0017] In some embodiments, the aerogel composite material is a sheet-type aerogel composite material.
[0018] According to another aspect of the present application, an embodiment of the present application provides a method for preparing an aerogel composite material, the method comprising the following steps:
[0019] Prepare a sol and a polycondensation material respectively, and pump the sol under a first pressurizing pressure and the polycondensation material under a second pressurizing pressure into a mixing unit for mixing to obtain a catalytic sol;
[0020] Unwinding the base material coil, and dipping the catalytic sol into the base material under the action of the third pressurizing pressure and / or the pressure formed by the glue coating component to obtain the dipped base material;
[0021] During the process of the catalytic sol in the impregnated matrix material transforming into gel, the thickness of the impregnated matrix material is measured to obtain a composite gel;
[0022] The composite gel is subjected to aging, cutting, replacement and drying in sequence to obtain the aerogel composite material.
[0023] In some embodiments, the preparation of the sol specifically includes: mixing an organic silane compound, an alcohol solvent, water and a hydrolyzing agent, and reacting to obtain a sol.
[0024] In some embodiments, the reaction temperature is 25-45° C., and the reaction time is 4 h to 6 h.
[0025] In some embodiments, the mass ratio of the organosilane compound, the alcohol solvent, water and the hydrolyzing agent is (0.8-1.5): (0-2): (0.5-8): (0.001-0.06).
[0026] In some embodiments, the organosilane compound includes at least one of ethyl orthosilicate, methyl orthosilicate, butyl orthosilicate, isopropyl orthosilicate or alkyl alkoxy silane, wherein the alkyl alkoxy silane includes at least one of methyltrimethoxysilane, dimethyldimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, vinyltriethoxysilane, propyltrimethoxysilane or propyltriethoxysilane.
[0027] In some embodiments, the hydrolyzing agent is an aqueous solution of an acidic compound, and the acidic compound includes at least one of hydrochloric acid, phosphoric acid, sulfuric acid, nitric acid, boric acid, formic acid, acetic acid or citric acid.
[0028] In some embodiments, the preparation of the polycondensation material specifically includes: uniformly mixing a polycondensation agent, a sunscreen and a phase change heat storage material to obtain the polycondensation material.
[0029] In some embodiments, the alkaline compound is first mixed with water and stirred for 3 to 10 minutes to obtain a polycondensation agent, and then a sunscreen and a phase change heat storage material are added and mixed and stirred for 5 to 30 minutes.
[0030] In some embodiments, the mass ratio of the alkaline compound to water is (0.01-0.2):1.
[0031] In some embodiments, the alkaline compound includes at least one of sodium hydroxide, potassium hydroxide, ammonia, ammonium fluoride, ammonium bicarbonate, sodium carbonate, sodium bicarbonate, ethanolamine, diethanolamine, methylamine, dimethylamine, ethylamine, diethylamine, propylamine, dipropylamine, isopropanolamine, aniline, o-phenylenediamine, m-phenylenediamine or p-phenylenediamine.
[0032] In some embodiments, the sunscreen includes at least one of titanium dioxide, silicon carbide, zirconium oxide, yttrium oxide, carbon black, potassium titanate whiskers, magnesium hydroxide, aluminum hydroxide, vermiculite or calcium carbonate.
[0033] In some embodiments, the phase change heat storage material includes at least one of an inorganic phase change heat storage material, an organic phase change heat storage material, and a composite phase change heat storage material.
[0034] Optionally, the inorganic phase change heat storage material includes crystalline hydrated salts and molten salts; the organic phase change heat storage material includes waxes; the composite phase change heat storage material includes capsules, composite porous matrices, inorganic nanocomposites and organic nanocomposites.
[0035] In some embodiments, the sol and the polycondensation material are mixed in the mixing unit for 5 seconds to 20 seconds.
[0036] In some embodiments, the first pressurizing pressure ranges from 0.1 to 7 MPa.
[0037] In some embodiments, the second pressurizing pressure ranges from 0.1 to 7 MPa.
[0038] In some embodiments, the volume ratio of the sol to the condensation material is (0.2-5):1.
[0039] In some of the embodiments, during the process of immersing the catalytic sol into the base material under the action of the third pressurizing pressure and / or the pressure formed by the glue coating component, a negative pressure device is used to form a local negative pressure area in the base material.
[0040] In some of the embodiments, during the process of immersing the catalytic sol into the base material under the action of the third pressurizing pressure and / or the pressure formed by the glue coating component, an ultrasonic vibration device is used to heat and apply ultrasonic vibration to the base material containing the catalytic sol.
[0041] In some embodiments, the third pressurizing pressure ranges from 0.1 to 7 MPa.
[0042] In some of the embodiments, the thickness is determined by respectively providing a first rolling mechanism and a second rolling mechanism on both side surfaces of the base material after the dipped resin.
[0043] In some embodiments, the aging is microwave aging, the temperature of the microwave aging is 60 to 75° C., and the time of the microwave aging is 20 min to 60 min.
[0044] In some embodiments, the drying is performed by supercritical drying, the supercritical drying temperature is 40 to 65° C., the drying pressure is 8 to 15 MPa, and the drying time is 6 to 12 hours.
[0045] In some of the embodiments, between the slitting and the replacement, the steps of arranging and flipping the sheets are also included.
[0046] In some of the embodiments, after the drying, the steps of sheet flipping, sheet sorting and sheet inspection are also included.
[0047] Implementing the technical solution of the present invention has at least the following beneficial effects:
[0048] In the embodiment of the present application, the provided aerogel composite material comprises a matrix material and an aerogel material, wherein the aerogel material comprises a silica aerogel, a sunscreen and a phase change heat storage material (also referred to as a phase change energy storage material); in the preparation method, the polycondensation agent can act on the sol to form a catalytic sol, and can also be used to adjust and form a gel having specific nanoscale three-dimensional network structure characteristic parameters, but the polycondensation agent will be washed out during the subsequent drying process of the aerogel preparation, so the aerogel composite material does not contain a polycondensation agent, and the sunscreen can be used to reduce the infrared radiation effect of the aerogel composite sheet at high temperature, and play a high temperature heat insulation role. The phase change heat storage material uses its own phase change energy storage (heat storage) effect to store part of the heat generated by the aerogel composite sheet during the thermal runaway process. The aerogel composite material has a high filling rate through the matching arrangement of the above materials, which is conducive to improving the performance of the aerogel composite sheet, not only effectively playing a role of heat insulation, but also reducing the risk of thermal runaway of the power battery of electric vehicles.
[0049] The preparation method of the provided aerogel composite material is to pump the prepared sol and polycondensation material into a mixing unit under pressure for rapid mixing to obtain a catalytic sol, and then immerse the catalytic sol into a matrix material under the pressure of a third pressurizing pressure and / or the pressure formed by a coating component, and then the thickness of the catalytic sol in the matrix material after the immersion is determined during the process of transforming the catalytic sol into a gel to obtain a composite gel, and then aging, cutting, replacement and drying are performed in sequence. Thus, by adopting sol pressurization, polycondensation material pressurization and pressure continuous feeding rapid mixing technology, under a certain pressure (such as 0.1-7MPa pressure), the sol and the polycondensation material are continuously pumped into the mixing unit for rapid, continuous and uniform mixing, and the catalytic sol is rapidly immersed in the pores of the matrix material under the pressure of the third pressurizing pressure and / or the pressure formed by the coating component, the immersion effect and immersion speed can be improved, and the filling rate of the aerogel can be improved.
[0050] In a preferred embodiment of the present invention, a negative pressure device is also used. The negative pressure device can be used to form a local negative pressure area on the surface and / or inside of the base material, which significantly increases the driving force for dipping, and promotes the catalytic sol of a certain pressure flowing out of the glue coating component to further quickly immerse into the base material such as fiber felt. The synergistic effect of pressurized dipping and negative pressure attraction greatly promotes the speed and depth of immersion of the catalytic sol into the fiber felt, and ensures the fullness of the dipping, reduces the surface defects caused by excess dipping, so the tape speed of the base material can be increased during the dipping process, and the dipping efficiency can be significantly improved. Thus, the effect of continuous and rapid dipping of the catalytic sol on the base material can be achieved, the consistency of the dipping quality and product performance can be ensured, a higher yield rate can be obtained, the surface quality of the product can be improved, the aerogel filling rate can be improved, and the thickness consistency of the aerogel composite sheet with a thicker substrate (thickness greater than 2 mm) can be improved. In addition, since the dipping pool commonly used in the prior art can be omitted, the amount of sol used is greatly saved, the excess dipping is reduced, and the production cost is reduced.
[0051] Additional aspects and advantages of the present application will be given in part in the following description, and in part will become obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 Shown is a schematic structural diagram of an aerogel composite material provided by an embodiment of the present invention.
[0053] Figure 2 Shown is a schematic flow chart of a method for preparing an aerogel composite material provided by an embodiment of the present invention.
[0054] Figure 3 Shown is a schematic flow chart of another method for preparing an aerogel composite material provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0055] The present application is further described below in conjunction with specific embodiments. It should be understood that these embodiments of the present application are only used to illustrate the present application and are not used to limit the scope of the present application.
[0056] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0057] Hereinafter, the embodiments of the aerogel composite material and its preparation method, etc. of the present application are specifically disclosed in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0058] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0059] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0060] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0061] As analyzed in the background technology, the existing preparation methods or equipment of aerogel composite materials still have certain shortcomings, especially regarding the problem of how to control thickness consistency, and no effective solution has been proposed. For example, in the related art, in order to reduce the waste of aerogel composite materials and the dust pollution caused to the processing environment by aerogel powder falling off the aerogel composite materials, the fiber substrate can be cut into the required size before producing aerogel composite sheets, which can also greatly save costs. For example, the sheet aerogel production gel device disclosed in the patent with publication number CN213972060U, or the preparation method and equipment of gel felt disclosed in the patent with announcement number CN114477949A, can reduce the dust pollution caused to the processing environment by aerogel powder, but failed to propose effective improvements in the uniform impregnation, surface quality defects and thickness consistency of composite sheets with a thickness of more than 1 mm.
[0062] For example, the related art adopts continuous combination of sol and gel additive to form catalytic sol, combines the fiber substrate with the catalytic sol at a predetermined rate and gels on the conveyor belt to form a gel sheet, but in actual production, the catalytic sol cannot be fully immersed in the fiber substrate, and there is often a phenomenon of uneven impregnation, resulting in a large dispersion of the thermal insulation performance of the aerogel product. In addition, the related art adopts measures to increase the amount of catalytic sol used to achieve full impregnation, but the excess impregnation amount will be left on the conveyor belt and form gel solid blocks (or powder) on the conveyor belt, which will cause device process failures. The gel solid blocks on the conveyor belt will also partially adhere to the gel felt produced subsequently, resulting in wrinkles, pits, breakage and other surface quality problems on the surface of the aerogel composite product. Furthermore, the existing coiled aerogel composite felt production device cannot be efficiently applied to the production of aerogel composite sheets, and the aerogel composite sheet has the disadvantages of easy surface defects, easy dislocation and difficult to stretch after curling during the production process of aerogel composite materials due to its lack of continuity.
[0063] Therefore, seeking to achieve a universal aerogel composite sheet with high thickness consistency, good surface quality, high aerogel filling rate, and a production process that can save the leveling process will be the key to achieving high-quality aerogel composite products for new energy electric vehicle power batteries, etc. Furthermore, if continuous production can be achieved, production efficiency can be further improved. Therefore, the use of a production method that is suitable for aerogel composite sheets with high production efficiency, high thickness consistency, and good surface quality, or a production method that can also be produced continuously, can ensure a higher yield and low production cost.
[0064] In view of this, the embodiment of the present application provides a method for preparing an aerogel composite material, which mainly forms a catalytic sol by dipping the sol and gel polycondensation agent under negative pressure and realizing gelation under pressure constraint, so as to achieve the purpose of high thickness consistency, good surface quality, high aerogel filling rate, high production efficiency, etc. of the aerogel composite sheet, and can save the subsequent leveling process, significantly improve the yield of the aerogel composite sheet, and reduce the production cost. The specific technical solution is described below.
[0065] In some embodiments, an aerogel composite material is provided, and the provided aerogel composite material can be used in the fields of batteries such as power batteries, for example, for thermal insulation between power battery cells; of course, in addition to this, the aerogel composite material can also be used in other fields, and the embodiments of the present application do not impose specific restrictions on the specific usage scenarios and working conditions of the aerogel composite material.
[0066] See also Figures 1 to 3 As shown, in some embodiments, an aerogel composite material is provided, the aerogel composite material comprising:
[0067] Base material; and
[0068] an aerogel material on an outer surface of a matrix material and / or impregnated into the matrix material;
[0069] Among them, the aerogel material includes silica aerogel, sunscreen and phase change heat storage material.
[0070] The provided aerogel composite material comprises a matrix material and an aerogel material, wherein the aerogel material comprises a silica aerogel, and comprises a sunscreen and a phase change heat storage material. Among them, a polycondensation agent is required in the process of preparing the aerogel composite material, and the polycondensation agent can be used to act on the sol to form a catalytic sol, and can also be used to adjust and form a gel body with specific nanoscale three-dimensional network structure characteristic parameters, but the polycondensation agent will be washed out in the subsequent drying process of the aerogel preparation, so the final aerogel composite product does not contain a polycondensation agent, and the sunscreen can be used to reduce the infrared radiation effect of the aerogel composite sheet at high temperature, and play a high-temperature heat insulation role. The phase change heat storage material uses its own phase change energy storage effect to store part of the heat generated by the aerogel composite sheet during the thermal runaway process. The aerogel composite material has a high filling rate through the matching setting of the above materials, which is conducive to improving the performance of the aerogel composite sheet, not only effectively playing a role of heat insulation, but also reducing the risk of thermal runaway of the power battery of electric vehicles.
[0071] It should be noted that, in the present application, the matrix material may include a fiber material and / or a 3D foam material.
[0072] In some embodiments, the composition formed by the above-mentioned sunscreen, phase change heat storage material and condensation agent can be called a condensation material, wherein the condensation agent includes an alkaline compound, and the alkaline compound includes, but is not limited to, any one or more combinations of sodium hydroxide, potassium hydroxide, ammonia water, ammonium fluoride, ammonium bicarbonate, sodium carbonate, sodium bicarbonate, ethanolamine, diethanolamine, methylamine, dimethylamine, ethylamine, diethylamine, propylamine, dipropylamine, isopropanolamine, aniline, o-phenylenediamine, m-phenylenediamine or p-phenylenediamine.
[0073] In some embodiments, the sunscreen includes, but is not limited to, any one or more combinations of titanium dioxide, silicon carbide, zirconium oxide, yttrium oxide, carbon black, potassium titanate whiskers, magnesium hydroxide, aluminum hydroxide, vermiculite or calcium carbonate. Optionally, the titanium dioxide is preferably rutile.
[0074] In some embodiments, the phase change heat storage material includes, but is not limited to, any one or more combinations of inorganic phase change heat storage materials, organic phase change heat storage materials, and composite phase change heat storage materials.
[0075] As examples, inorganic phase change heat storage materials include crystalline hydrated salts and molten salts; organic phase change heat storage materials include waxes; composite phase change heat storage materials include capsules, composite porous matrices, inorganic nanocomposites, and organic nanocomposites.
[0076] It should be pointed out that the present application does not limit the specific type of phase change heat storage material. It can adopt conventional inorganic, organic, composite and other phase change heat storage materials. As long as it can be used to store part of the heat generated by the aerogel composite sheet at low temperature during thermal runaway, it does not limit the purpose of the present invention.
[0077] In some embodiments, the mass percentage of the sunscreen in the aerogel material is 30% to 160%.
[0078] In some embodiments, the mass proportion of the phase change heat storage material in the aerogel material is 0% to 50%.
[0079] It should be pointed out here that the mass proportion of sunscreen agents, phase change heat storage materials, etc. in aerogel materials can be adjusted according to actual needs, such as being within the above-mentioned proportion range, or can be adaptively adjusted to exceed this range according to different application requirements.
[0080] In the embodiment of the present application, the aerogel composite material is a sheet-type aerogel composite material.
[0081] In some embodiments, the matrix material includes fiber felt and / or foam material (3D foam material); for example, the matrix material may be fiber felt, or may be foam material.
[0082] See also Figures 1 to 3 As shown, in some embodiments, a method for preparing an aerogel composite material is provided, the method comprising the following steps:
[0083] Prepare a sol and a polycondensation material respectively, and pump the sol under a first pressurizing pressure and the polycondensation material under a second pressurizing pressure into a mixing unit for mixing to obtain a catalytic sol;
[0084] Unwinding the base material coil, and dipping the catalytic sol into the base material under the action of the third pressurizing pressure and / or the pressure formed by the glue coating component to obtain a dipped base material;
[0085] During the process of the catalytic sol in the matrix material being impregnated with gel being transformed into gel, the thickness of the matrix material after being impregnated with gel is measured to obtain a composite gel;
[0086] The composite gel is subjected to aging, cutting, replacement and drying in sequence to obtain an aerogel composite material.
[0087] In the present application, a method for preparing an aerogel composite material realizes the effect of high thickness consistency of an aerogel composite sheet by forming a catalytic sol by a sol and a gel condensation agent under pressure constraint to achieve gelation. The aerogel composite sheet has good surface quality and a high aerogel filling rate. In addition, the production efficiency is high, continuous production is possible, and the subsequent leveling process can be omitted, which can significantly improve the yield of aerogel composite sheets.
[0088] Specifically, in the embodiment of the present application, the preparation method of the aerogel composite material provided is to pump the prepared sol and the polycondensation material into the mixing unit under pressure for rapid mixing to obtain a catalytic sol, and then immerse the catalytic sol in the matrix material under the pressure of the third pressurizing pressure and / or the pressure formed by the coating component, and then the thickness of the catalytic sol in the matrix material after the dip is determined during the process of transformation to gel to obtain a composite gel material, and then aging, cutting, replacement and drying are carried out in sequence. Thus, by adopting the sol pressurization, polycondensation material pressurization and pressure continuous feeding rapid mixing technology, under a certain pressure (0.1-7MPa pressure), the sol and the polycondensation material are continuously pumped into the mixing unit for rapid, continuous and uniform mixing, and the catalytic sol with a certain pressure (about 0.1-7MPa) is formed by the third pressurizing pressure and / or the coating component, which can quickly immerse into the pores of the matrix material, improve the dipping effect, and improve the aerogel filling rate.
[0089] In the preferred implementation of the embodiment of the present invention, a negative pressure device is also used. The negative pressure device can be used to form a local negative pressure area on the surface and / or inside of the base material, which significantly increases the driving force for dipping, promotes the sol of a certain pressure flowing out of the coating component to further quickly immerse into the base material such as fiber felt, greatly promotes the speed and depth of the catalytic sol immersing into the base material, and ensures the fullness of the dipping. Therefore, the tape speed of the base material can be increased during the dipping process, and the existing tape speed of 2M / min can be increased to a tape speed of more than 20M / min, which significantly improves the dipping efficiency. Thus, while maintaining the synergistic effect of the coating of a certain pressure and the negative pressure attraction in the substrate, the effect of continuous and rapid dipping of the catalytic sol on the base material can be achieved, the consistency of the dipping quality and product performance is ensured, a higher yield is obtained, the surface quality of the product can be improved, the aerogel filling rate can be improved, and a solid foundation can be laid for achieving high consistency in the thickness of the aerogel composite sheet. In addition, since the dipping pool commonly used in the prior art can be omitted, the amount of sol used is greatly saved, and the production cost is reduced.
[0090] Therefore, the present application can improve the filling rate of the catalytic sol, ensure the consistency of the impregnation quality and product performance, improve the surface quality of the product, and lay a solid foundation for achieving high consistency in thickness of aerogel composite sheets by using the above-mentioned pressure-constrained glue coating method through a glue coating machine; further, the present invention also provides a gel thickness setting device, which includes a double-belt rolling mechanism, which can effectively control the thickness. Therefore, through the coordinated setting of the above-mentioned glue coating machine and the gel thickness setting device, the problem that the current aerogel composite sheet production method is difficult to ensure the consistency of the composite sheet thickness can be effectively alleviated, and the thickness consistency of the aerogel composite sheet can be improved, the surface quality can be improved, and the production efficiency is relatively high.
[0091] In some specific embodiments, the method for preparing the aerogel composite material specifically includes the following steps S10 to S100.
[0092] Step S10: preparing sol.
[0093] In some embodiments, preparing the sol specifically includes: mixing an organic silane compound, an alcohol solvent, water and a hydrolyzing agent, and obtaining the sol after reaction.
[0094] As an example, a sol preparation device can be used to add an organosilane compound, an alcohol solvent, water and a hydrolyzing agent to a stirring tank of the sol preparation device according to the ratio requirements for stirring and mixing. Preferably, according to the ratio requirements, the organosilane compound, the alcohol solvent and water are first weighed, the three are evenly mixed, and then the hydrolyzing agent is added thereto and stirred evenly to obtain a silica sol.
[0095] In some embodiments, the reaction temperature is 25-45° C., and the reaction time is 4 h to 6 h.
[0096] In some embodiments, the mass ratio of the organosilane compound, the alcohol solvent, water and the hydrolyzing agent is (0.8-1.5):(0-2):(0.5-8):(0.001-0.06).
[0097] Preferably, the mass ratio of the organosilane compound, the alcohol solvent, water and the hydrolyzing agent is 1:0.3:3.33:0.0035.
[0098] Optionally, alcohol solvents include but are not limited to methanol, ethanol, etc.
[0099] In some embodiments, the organosilane compound includes at least one of ethyl orthosilicate, methyl orthosilicate, butyl orthosilicate, isopropyl orthosilicate or alkyl alkoxysilane, wherein the alkyl alkoxysilane includes at least one of methyltrimethoxysilane, dimethyldimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, vinyltriethoxysilane, propyltrimethoxysilane or propyltriethoxysilane.
[0100] In some embodiments, the hydrolyzing agent is an aqueous solution of an acidic compound, and the acidic compound includes but is not limited to at least one of hydrochloric acid, phosphoric acid, sulfuric acid, nitric acid, boric acid, formic acid, acetic acid or citric acid.
[0101] Optionally, the weight concentration of the acidic compound is 1% to 15%, for example, about 5%.
[0102] Step S20: preparing polycondensation material.
[0103] In some embodiments, preparing the polycondensation material specifically includes: mixing and stirring the alkaline compound and water to obtain a polycondensation agent, and mixing and stirring the polycondensation agent with a sunscreen and a phase change heat storage material to obtain a polycondensation material.
[0104] Specifically, in some embodiments, a condensation material preparation device can be used to first mix the alkaline compound with water and stir for 3 minutes to 10 minutes according to the ratio requirements to obtain a condensation agent, and then add a sunscreen agent and a phase change heat storage material and mix and stir for 5 minutes to 30 minutes to prepare a condensation agent mixed liquid containing a sunscreen agent and a phase change heat storage material.
[0105] In some embodiments, the mass ratio of the alkaline compound to water is (0.01-0.2):1.
[0106] In some embodiments, the mass ratio of the sunscreen agent to the polycondensation agent is (0.1-1): 1. Preferably, the mass ratio of the sunscreen agent to the polycondensation agent is (0.1-0.5):1.
[0107] In some embodiments, the mass ratio of the phase change heat storage material to the polycondensation agent is (0-0.5): 1. Preferably, in some embodiments, the mass ratio of the phase change heat storage material to the polycondensation agent is (0.1-0.5): 1.
[0108] In some embodiments, the condensation agent includes an alkaline compound, which includes, but is not limited to, any one or more combinations of sodium hydroxide, potassium hydroxide, ammonia, ammonium fluoride, ammonium bicarbonate, sodium carbonate, sodium bicarbonate, ethanolamine, diethanolamine, methylamine, dimethylamine, ethylamine, diethylamine, propylamine, dipropylamine, isopropanolamine, aniline, o-phenylenediamine, m-phenylenediamine or p-phenylenediamine.
[0109] In some embodiments, the sunscreen includes, but is not limited to, any one or more combinations of titanium dioxide, silicon carbide, zirconium oxide, yttrium oxide, carbon black, potassium titanate whiskers, magnesium hydroxide, aluminum hydroxide, vermiculite or calcium carbonate. Optionally, the titanium dioxide is preferably rutile.
[0110] In some embodiments, the phase change heat storage material includes, but is not limited to, any one or more combinations of inorganic phase change heat storage materials, organic phase change heat storage materials, and composite phase change heat storage materials.
[0111] As examples, inorganic phase change heat storage materials include crystalline hydrated salts and molten salts; organic phase change heat storage materials include waxes; composite phase change heat storage materials include capsules, composite porous matrices, inorganic nanocomposites, and organic nanocomposites.
[0112] Thus, the provided polycondensation material forms a catalytic sol through the action of a polycondensation agent on the sol, which is used to adjust and form a gel body with specific nanoscale three-dimensional network structure characteristic parameters; the sunscreen is used to reduce the infrared radiation effect of the aerogel composite sheet at high temperature, thereby playing a high-temperature heat insulation role; in addition, the phase change heat storage material utilizes its own phase change energy storage effect to store part of the heat generated by the aerogel composite sheet during thermal runaway.
[0113] Step S30: rapid mixing.
[0114] The prepared sol is pumped into a mixing unit under a first pressurizing pressure and the prepared polycondensation material is pumped into a mixing unit under a second pressurizing pressure for mixing to obtain a catalytic sol.
[0115] As an example, the prepared sol may be pumped into the mixing unit by a first pressure pump, and the prepared polycondensation material may be pumped into the mixing unit by a second pressure pump, and the sol and the polycondensation material may be mixed in the mixing unit.
[0116] Optionally, the outlet of the sol preparation device can be connected to a sol pressurizing device, which is used to pressurize and heat the output sol and monitor the physical properties of the sol. Optionally, the sol pressurizing device includes a sol intermediate tank, a first pressurizing pump, a first mixing and heating mechanism, and a first detection component, etc. The discharge port of the sol preparation device is connected to the inlet of the sol intermediate tank, and the discharge port of the sol intermediate tank is connected to the first pressurizing pump; the first mixing and heating mechanism and the third detection component are respectively arranged in the sol intermediate tank, and are respectively used to mix, heat and detect the sol.
[0117] Optionally, the outlet of the polycondensation material preparation device can be connected to a polycondensation material pressurizing device, which can be used to output a pressurized and heated polycondensation agent mixed solution containing a sunscreen and a phase change heat storage material and monitor physical property indicators. Optionally, the polycondensation material pressurizing device includes a polycondensation material intermediate tank, a second pressurizing pump, a second mixing and heating mechanism, and a second detection component. The discharge port of the polycondensation material preparation device is connected to the inlet of the polycondensation material intermediate tank, and the discharge port of the polycondensation material intermediate tank is connected to the second pressurizing pump; the second mixing and heating mechanism and the second detection component are respectively arranged in the polycondensation material intermediate tank, and are respectively used to mix, heat and detect the polycondensation material.
[0118] Optionally, in the sol pressurizing device and the polycondensation material pressurizing device, both the first pressurizing pump and the second pressurizing pump may be plunger diaphragm pumps.
[0119] Optionally, in the sol pressurizing device and the condensation material pressurizing device, the first mixing and heating mechanism and the second mixing and heating mechanism may both adopt ultrasonic vibration devices.
[0120] Optionally, the sol pressurizing device further comprises a first cleaning mechanism for cleaning the sol pressurizing device and a first online flow meter for online metering of the sol content. Optionally, the polycondensation material pressurizing device further comprises a second cleaning mechanism for cleaning the polycondensation material pressurizing device and a second online flow meter for online metering of the polycondensation material content.
[0121] Thus, in the embodiment of the present application, the sol pressurizing device mainly includes a sol intermediate tank, a first pressurizing pump, a first mixing and heating mechanism, a first detection component, a first cleaning mechanism and a first online flow meter. Among them, the sol intermediate tank can be used as a container for continuously storing sol at a constant volume, and a vibrating rod of an ultrasonic vibration device, a detection instrument, etc. are provided on the container. The first pressurizing pump can be a plunger diaphragm pump, which can be used to pressurize the output sol and keep the sol under pressure to be transported to the mixer. The first mixing and heating mechanism can be an ultrasonic vibration device, which can be used to heat the sol in situ to quickly output a sol at 40 to 55°C; optionally, the ultrasonic vibration device includes an ultrasonic generator and a vibrating rod connected to the ultrasonic generator, and the vibrating rod can be inserted into the sol, and the cavitation effect caused by the instantaneous high temperature and high pressure generated by the high-frequency vibration of the ultrasonic wave in the sol is used to quickly mix and heat the sol in situ. The first detection component (detection instrument) may include a temperature sensor, a pH value detector, an ultrasonic level meter, etc., which can be used to monitor the temperature, pH value and liquid level of the sol. The first cleaning mechanism can be arranged on the continuous sol pressurizing device to regularly clean and remove the residual materials in the pressurizing system. The first online flow meter can be arranged on the conveying pipeline to measure the input amount of the pressurized sol online.
[0122] In the embodiment of the present application, the condensation material pressurizing device mainly includes an intermediate tank of condensation material, a second pressurizing pump, a second mixing and heating mechanism, a second detection component, a second cleaning mechanism and a second online flowmeter. Among them, the intermediate tank of the condensation agent can be used for a container for storing a condensation agent mixed solution containing a sunscreen and a phase change heat storage material at a constant volume, and an ultrasonic vibrating rod, a detection instrument, etc. are provided on the container. The second pressurizing pump can be a plunger diaphragm pump, which is used to pressurize the output condensation agent mixed solution containing a sunscreen and a phase change heat storage material, and keep it under pressure to be transported to the mixing unit. The second mixing and heating mechanism can be an ultrasonic vibration device, which is used to heat the condensation agent mixed solution containing a sunscreen and a phase change heat storage material in situ, so as to quickly output the pressurized and heated (40 to 55 ° C) condensation agent mixed solution containing a sunscreen and a phase change heat storage material, which may include an ultrasonic generator and a vibrating rod connected to the ultrasonic generator, and the vibrating rod is inserted into the condensation agent mixed solution, and the cavitation effect caused by the instantaneous high temperature and high pressure generated by the high-frequency vibration of the ultrasonic wave in the condensation agent mixed solution is used to quickly mix and heat the condensation agent mixed solution in situ. The second detection component (detection instrument) may include a temperature sensor, a pH value detector, an ultrasonic level meter, etc., which can be used to monitor the temperature, pH value and liquid level of the polycondensation agent mixture. The second cleaning mechanism can be arranged on the continuous polycondensation agent mixture pressurizing device, and is used to regularly clean and remove the remaining materials in the pressurizing system. The second online flow meter can be arranged on the conveying pipeline, and is used to measure the input amount of the pressurized polycondensation agent mixture containing the sunscreen online.
[0123] It should be pointed out that in the present application, the specific structure or type of the cleaning mechanism, online flow meter and other device components can refer to the prior art, as long as they can be used to clean the residual materials in the device, or can realize online flow detection. This embodiment does not limit the specific structural form of these components.
[0124] In the embodiment of the present application, the discharge port of the sol pressurizing device and the discharge port of the condensation material pressurizing device are respectively connected to the inlet of the mixing unit, and the discharge port of the mixing unit can be connected to the feed port of the glue coating component.
[0125] Preferably, the discharge port of the mixing unit can be connected to the feed port of the glue coating pressurizing mechanism, and the discharge port of the glue coating pressurizing mechanism is connected to the feed port of the glue coating component.
[0126] Optionally, the mixing unit may include a static mixer. Further, the mixing unit may also include a third cleaning mechanism for cleaning the static mixer.
[0127] The mixing unit of this embodiment is a rapid mixing device, which can be a static mixer. By placing a mixing unit with a specific structure on the pipeline, the three forces of "division", "conversion" and "reversal" are used to promote rapid mixing of the sol and the condensation agent mixture containing the sunscreen in the mixer in the pipeline.
[0128] In some embodiments, the sol and the polycondensation material are mixed in the mixing unit for a period of 5 seconds to 20 seconds.
[0129] In some embodiments, the sol is pressurized by a first pressurizing pump, and the pressure range of the first pressurizing pressure is 0.1-7 MPa.
[0130] In some embodiments, the polycondensation material is pressurized by a second pressurizing pump, and the second pressurizing pressure has a pressure range of 0.1 to 7 MPa.
[0131] In some embodiments, the volume ratio of the sol to the condensation material is (0.2-5):1.
[0132] Step S40, unwinding the rolled felt.
[0133] Optionally, the base material roll is unrolled on an unwinding device.
[0134] The unwinding device can be used to support the base material coil and unwind it continuously. The present application does not limit the specific structural form of the unwinding device, and conventional technology can be used.
[0135] Step S50: applying glue.
[0136] In step S50, the prepared catalytic sol is quickly immersed in the base material. For example, the catalytic sol is immersed in the base material under the action of the third pressurizing pressure and / or the pressure formed by the glue coating component to obtain the dipped base material.
[0137] In some embodiments, during the process of immersing the catalytic sol into the base material under the action of the third pressurizing pressure and / or the pressure formed by the glue coating component, a negative pressure device is used to form a local negative pressure area in the base material.
[0138] In some embodiments, during the process of immersing the catalytic sol into the base material under the action of the third pressurizing pressure and / or the pressure formed by the glue coating component, an ultrasonic vibration device is used to heat and apply ultrasonic vibration to the base material.
[0139] As an example, in the present application, the glue coating adopts a glue coating device, which includes a glue coating component and a negative pressure device. The glue coating device can be used for glue coating, that is, the glue coating device can be used to pressurize and convey the sol after rapid mixing and the polycondensation agent (catalytic sol) of the sunscreen matrix material coil to the glue coating component for rapid glue coating. Optionally, the glue coating device includes a third pressurizing mechanism, and further, the glue coating device can also include a glue coating box, a cleaning device, and a nitrogen sealing mechanism. In some preferred embodiments, the glue coating device can further include an ultrasonic vibration device when heating while pressurizing.
[0140] In the embodiment of the present application, the opposite ends of the glue coating box are provided with an inlet and an outlet for the base material to enter and exit, and the negative pressure device and the glue coating component can be located in the glue coating box. It can be understood that the glue coating box is a box with four sides sealed, and the opposite ends of the glue coating box, such as the left and right side walls of the glue coating box, are provided with an inlet and an outlet for the base material to enter and exit. In the glue coating box, the catalytic sol can be immersed in the base material by the glue coating component.
[0141] In the embodiment of the present application, the glue coating component includes a porous matrix glue coating head, which includes multiple groups of tubular glue coaters. The glue coating head is located inside the glue coating box and is connected to the third pressurizing mechanism or the mixing unit, and is used to quickly and evenly spray the formed catalytic sol of a certain pressure onto the surface of the moving base material and immerse it therein. The glue coating head is preferably a porous matrix narrow hole glue coating head, which is composed of multiple groups of tubular glue coaters, each of which has N uniformly distributed through holes with an aperture of no more than 1 mm, and is used to quickly and evenly spray the catalytic sol onto the base material. By adopting the porous matrix narrow hole coating head technology, the catalytic sol flowing out of the catalytic sol channel can be coated onto the surface of the base material in small amounts and multiple times, and the sprayed dipping amount and spraying pressure can be controlled, thereby reducing the surface defects of the dipping, achieving uniform dipping and appropriate gel filling depth, significantly improving the dipping effect and dipping speed, and eliminating the sol pool in conventional applications. The amount of sol used in production is greatly reduced, saving the cost of raw materials, greatly improving the utilization rate of the sol, and greatly reducing the scrap rate.
[0142] In the embodiment of the present application, the negative pressure device can be used to generate a negative pressure zone in a base material such as a fiber felt, and quickly immerse the catalytic sol into the base material. Optionally, the negative pressure device includes a negative pressure generator and a negative pressure distribution member connected to the negative pressure generator, the negative pressure distribution member is located in the coating box, and the negative pressure distribution member is arranged on the upper side and / or lower side of the base material such as the fiber felt, such as the negative pressure distribution member can be arranged on the upper side or lower side of the fiber felt.
[0143] The negative pressure uniform distribution member is used to continuously and quickly absorb the catalytic sol flowing out of the coating head into the base material. The negative pressure uniform distribution member can be arranged above or below the base material. The negative pressure uniform distribution member is provided with N uniform through holes on the surface of the uniform distribution plate for contacting the base material, and is connected to the negative pressure generator. When the negative pressure uniform distribution member is arranged above the surface of the base material, it needs to be arranged close to the coating head, and a local negative pressure zone is formed on the surface layer of the base material, which promotes the driving force of the catalytic sol coated on the surface of the base material to immerse into the negative pressure zone, greatly promotes the immersion speed of the catalytic sol into the base material, and ensures the fullness of the immersion. At this time, an ultrasonic vibration device can be arranged below the base material to in-situ heat the temperature of the catalytic sol immersed in the base material while coating the glue, in order to improve the sol penetration ability, and eliminate the bubbles that remain in the base material due to the sol not being discharged in time during the immersion process in the base material, so as to improve the immersion effect. When the negative pressure uniform distribution member is set below the surface of the base material, a local negative pressure zone is formed in the base material, which significantly increases the driving force for the catalytic sol to penetrate into the base material. This effect is the best, but the amount of catalytic sol is relatively large. In this case, a separate ultrasonic vibration box needs to be set in the forward direction of the base material outside the coating box.
[0144] In an embodiment of the present application, the gluing device further includes an ultrasonic vibration device, which is disposed in the gluing box and below the base material after gluing; in this case, the negative pressure uniform distribution member is disposed above the surface of the base material. In addition, an ultrasonic vibration device may be disposed outside the gluing box and in the forward direction of the base material after gluing, in which case the negative pressure uniform distribution member is disposed below the surface of the base material. Thus, the ultrasonic vibration device of the present application may be disposed below the base material after gluing inside the gluing box, or a separate ultrasonic vibration device may be disposed in the forward direction of the base material after gluing outside the gluing box.
[0145] An ultrasonic vibration device is arranged inside the glue coating box below the base material after dipping in glue, which is used to in-situ heat the temperature of the catalytic sol immersed in the base material, in order to improve the penetration ability of the catalytic sol and eliminate the bubbles that remain in the base material due to the catalytic sol not being discharged in time during the dipping process in the base material, thereby improving the dipping effect. It may include an ultrasonic generator and a vibration rod.
[0146] Optionally, the glue coating device may further include a nitrogen sealing device, such as providing a nitrogen sealing device on both the inlet side and the outlet side of the glue coating box.
[0147] Thus, based on the above settings, the present application adopts sol pressurization, polycondensation material pressurization and pressure continuous feeding rapid mixing technology, under a certain pressure (0.1-7MPa pressure), continuously pumps the sol and polycondensation material into a mixing device such as a static mixer, and performs rapid, continuous and uniform mixing, and forms a catalytic sol of a certain pressure (about 0.1-7MPa) through a glue coating pressurization mechanism and / or a glue coating component, which can quickly immerse into the pores of the base material. In addition, a negative pressure device is also used, and a local negative pressure zone can be formed on the surface and / or inside of the base material by using the negative pressure device, which significantly increases the driving force for dipping, promotes the catalytic sol of a certain pressure flowing out of the glue coating component to further quickly immerse into the base material such as fiber felt, greatly promotes the speed and depth of sol immersion into the fiber felt, and ensures the fullness of the dipping, so the tape speed of the base material can be increased during the dipping process, and the tape speed of the existing dipping pool process of 2M / min is increased to a tape speed of more than 20M / min, significantly improving the dipping efficiency. Thus, the effect of continuous and rapid impregnation of the catalytic sol on the matrix material can be achieved, the consistency of the impregnation quality and product performance can be ensured, a higher yield rate can be obtained, the surface quality of the product can be improved, the aerogel filling rate can be increased, and a solid foundation can be laid for achieving high consistency in the thickness of the aerogel composite sheet. In addition, since the impregnation pool commonly used in the prior art can be omitted, the amount of sol used can be greatly saved, and the production cost can be reduced.
[0148] Therefore, the present application can improve the filling rate of the catalytic sol by adopting the above-mentioned pressurized glue coating and negative pressure suction synergistic method, ensure the consistency of the dipping quality and product performance, improve the surface quality of the product, and lay a solid foundation for achieving high thickness consistency of aerogel composite sheets; further, the present invention also performs shaping and thickness determination in the process of transformation from sol to gel, such as using a gel thickness determination device including a double-belt rolling mechanism, which can effectively control the thickness. Therefore, through the synergistic cooperation of the above-mentioned glue coating method and gel thickness determination, the problem that the current aerogel composite sheet production system is difficult to ensure the thickness consistency of aerogel composite sheets can be effectively alleviated, the thickness consistency of aerogel composite sheets can be improved, the surface quality can be improved, and the production efficiency is relatively high.
[0149] Step S60: determining the thickness of the gel.
[0150] In step S60, the thickness of the matrix material after the dip is calibrated during the process of the catalyst sol in the matrix material after the dip to gel, so as to obtain a composite gel. For example, on a double belt roller press, gelation is performed under the pressure constraint formed between the moving upper and lower rollers, and the catalyst sol entering the double belt roller press achieves gelation during the process.
[0151] In some embodiments, the thickness is determined by respectively providing a first rolling mechanism and a second rolling mechanism on both side surfaces of the base material after the dip-coating.
[0152] As an example, the gel thickness setting device can be used to control the thickness of the base material after the gelling process. Optionally, the gel thickness setting device includes a pre-gel box and a double-belt roller gel thickness setting machine.
[0153] Exemplarily, the gel thickness setting device includes a double-belt rolling mechanism, which includes a first rolling mechanism and a second rolling mechanism respectively located on the two side surfaces of the base material after dipping. For example, the first rolling mechanism can be arranged on the upper side of the base material after dipping, and the second rolling mechanism can be arranged on the lower side of the base material after dipping. Optionally, the gel thickness setting device also includes a gel thickness setting box, and the opposite ends of the gel thickness setting box are provided with an inlet and an outlet for the base material after dipping, and the inlet side and the outlet side of the gel thickness setting box are respectively provided with a nitrogen sealing mechanism; the first rolling mechanism and the second rolling mechanism are located in the gel thickness setting box; and a detection component can be arranged in the gel thickness setting box.
[0154] Optionally, the gel thickness setting device further comprises a pre-gel box, and along the direction of conveying the fiber material, the glue coating machine, the pre-gel box, the double-belt roller pressing mechanism, the aging device and the slicer are sequentially arranged. The opposite ends of the pre-gel box are provided with an inlet and an outlet for the matrix material after the glue is impregnated; the inlet side and the outlet side of the pre-gel box are respectively provided with a third nitrogen sealing mechanism and a fourth nitrogen sealing mechanism.
[0155] In the embodiment of the present application, the gel thickness setting device mainly includes a pre-gel box and a double-belt roller-pressed gel thickness setting machine, and may further include a nitrogen sealing device, etc. Among them, the double-belt roller-pressed gel thickness setting machine includes a gel thickness setting box, a double-belt roller pressing mechanism, detection instruments and equipment, etc., wherein the double-belt roller pressing mechanism and the detection instruments and equipment can be arranged in the gel thickness setting box, and the process of sol-to-gel transformation can be realized in the gel thickness setting box, that is, the process of catalytic sol-to-gel transformation after rapid dipping can be realized, and the thickness of the matrix material can be shaped and determined at the same time.
[0156] Among them, in the above-mentioned gel thickness determination device, the pre-gel box is a box sealed on all sides, and the opposite ends of the pre-gel box are provided with an inlet and an outlet for the matrix material after the gelling; for example, the left wall of the pre-gel box is provided with an inlet for the matrix material after the gelling, and the right wall of the pre-gel box is provided with an outlet for the matrix material after the gelling. Through the setting of the pre-gel box, it can be used to obtain the gel nucleation incubation time of the catalytic sol immersed in the matrix material. There is a nitrogen sealing device at the inlet and outlet of the pre-gel box, and the setting of the nitrogen sealing mechanism can be used to prevent the steam in the box from escaping out of the box.
[0157] In the above-mentioned gel thickness setting device, the matrix material impregnated with glue output from the pre-gel box can enter the gel thickness setting box. The gel thickness setting box is a box sealed on all sides, and the opposite ends of the gel thickness setting box are provided with an inlet and an outlet for the matrix material impregnated with glue to enter and exit; for example, the left wall of the gel thickness setting box is provided with an inlet for the matrix material impregnated with glue to enter, and the right wall of the gel thickness setting box is provided with an outlet for the matrix material impregnated with glue to exit. The inlet side and the outlet side of the gel thickness setting box are respectively provided with nitrogen sealing mechanisms, and the setting of the nitrogen sealing mechanisms can prevent air from entering and steam from leaking out.
[0158] In the above-mentioned gel thickness setting device, the double-belt rolling mechanism is located in the gel thickness setting box, and is used to shape and set the thickness of the base material of the dipped gel, that is, the composite gel body, during the process of the catalytic sol being transformed into gel after rapid dip. Optionally, the double-belt rolling mechanism includes a first rolling mechanism and a second rolling mechanism, and may also include a frame and a height adjustment mechanism, etc.
[0159] The first rolling mechanism, the second rolling mechanism and the height adjustment mechanism can all be arranged on a frame, and the frame can be used to install and support the first rolling mechanism, the second rolling mechanism and the height adjustment mechanism.
[0160] Optionally, the first rolling mechanism includes a first active roller, a first passive roller, a first pressure plate (or a first support plate) and a first rolling belt, the first active roller and the first passive roller drive the first rolling belt to move, and the first rolling belt is connected to the first pressure plate; the second rolling mechanism includes a second active roller, a second passive roller, a second pressure plate (or a second support plate) and a second rolling belt, the second active roller and the second passive roller drive the second rolling belt to move, and the first rolling belt is connected to the first pressure plate. In the embodiment of the present application, the first rolling mechanism and the second rolling mechanism can be respectively located on the upper and lower surfaces of the base material after the dip, and are used to press the upper and lower surfaces of the base material containing the catalytic sol through the upper and lower rollers, and maintain the required gap thickness between the upper and lower rollers according to the set thickness requirements. The above-mentioned first rolling mechanism includes a first active roller, a first passive roller and a first pressure plate (or a first support plate), that is, the upper rolling mechanism includes an upper active roller, an upper passive roller and an upper pressure plate (or an upper support plate), and the above-mentioned second rolling mechanism includes a second active roller, a second passive roller and a second pressure plate (or a second support plate), that is, the lower rolling mechanism includes a lower active roller, a lower passive roller and a lower pressure plate (or a lower support plate). Therefore, through the setting of the upper and lower active rollers and the upper and lower passive rollers, it can be used to drive the movement of the upper and lower rolling belts, maintain a certain flatness, and form a preset height between the upper and lower rolling belts. Furthermore, the above-mentioned first rolling mechanism, i.e., the upper rolling mechanism, also includes a first rolling belt, i.e., the upper rolling belt, and the above-mentioned second rolling mechanism, i.e., the lower rolling mechanism, also includes a second rolling belt, i.e., the lower rolling belt. The first rolling belt connects the first active roller, the first passive roller and the first pressure plate (or the first support plate), and the second rolling belt connects the second active roller, the second passive roller and the second pressure plate (or the second support plate). The upper and lower rolling belts can be driven to move by the upper and lower active rollers and the upper and lower passive rollers.
[0161] It should be understood that in order to drive the first active roller and the second active roller to move, a driving mechanism or a transmission mechanism is also included, such as an upper and lower pressure roller transmission device for providing power for the upper and lower active and passive rollers to move, which can be driven by a motor, etc. It should be pointed out that the specific structure or form of the driving mechanism or the transmission mechanism is not limited in this embodiment, and a device such as a motor that can be used to drive the pressure roller to move, which is well known in the art, can be used.
[0162] Optionally, the first rolling mechanism and the second rolling mechanism are respectively connected to a height adjustment mechanism; through the setting of the height mechanism, it can be used to adjust the flatness and height between the first rolling mechanism and the second rolling mechanism. Optionally, the height adjustment mechanism may include a servo motor, an electric cylinder, a grating ruler, etc., and the servo motor adjusts the up and down movement of the electric cylinder lead screw and drives the up and down movement of the grating ruler. The displacement between the first rolling mechanism and the second rolling mechanism is measured by the grating ruler, thereby achieving the purpose of adjusting the height between the first rolling mechanism and the second rolling mechanism.
[0163] Optionally, the gel thickness setting box is provided with a detection instrument, that is, a fifth detection component is provided in the gel thickness setting box. The fifth detection component may be, for example, a temperature sensor, a gas concentration sensor, etc., which can be used to detect the temperature and gas concentration in the gel thickness setting box.
[0164] Therefore, the present application, through the setting of the above-mentioned gel thickness setting device, utilizes double-belt roller pressing to apply surface pressure on the upper and lower surfaces of the fiber composite gel felt. The pressure applied is more uniform than that applied by general roller pressing, and is more conducive to controlling the thickness, thereby helping to improve the thickness consistency of the sheet-type aerogel composite material.
[0165] Step S70: Aging.
[0166] In step S70, the composite gel obtained in step S60 is aged, preferably by microwave aging.
[0167] In some embodiments, the aging is microwave aging, the microwave aging temperature is 60-75° C., and the microwave aging time is 0.5 h to 1 h. That is, the aging treatment is performed under microwave heating at 60-75° C. for 20-60 min.
[0168] By controlling the temperature of the composite gel within the range of 60 to 75°C and aging for 20 to 60 minutes, the microporous structure of the gel can be reduced, the optimal pore structure can be enhanced, the permeability of the liquid phase in the gel and the mechanical properties of the gel can be increased, thereby achieving the effect of strengthening the gel skeleton.
[0169] Step S80: cutting.
[0170] In step S80, the aged continuous composite gel obtained in step S70 is cut into required sizes in both the longitudinal and transverse directions to obtain composite gel fiber sheets.
[0171] In this embodiment, the composite gel body transported by the aging device can enter the slicer, and the composite gel body can be sliced by the slicer (also called a slitting machine). Through this slicing step, the slicer can be used to cut the continuous composite gel body obtained from the base material according to the size requirements.
[0172] It should be noted that the embodiment of the present application does not limit the specific structural form of the slicer, as long as it can be used to cut the composite sheet according to the preset size. As an example, the slicer may include a slitting box, a cross-cutting mechanism, and a nitrogen sealing mechanism; more preferably, it also includes a longitudinal cutting mechanism.
[0173] It should be understood that the specific size of the composite gel sheet can be selected and set according to actual needs, and this application does not limit this.
[0174] Step S90: Replacement.
[0175] In step S90, the composite gel sheet obtained in step S80 is subjected to solvent replacement. The replacement step can be carried out using conventional techniques in the art.
[0176] Optionally, in an embodiment of the present application, between the slitting step S80 and the replacement step S90, the steps of arranging and flipping the composite gel sheet are also included. As an example, after the slicing step S80 and before the replacement step S90, the steps also include: the step of loading the composite gel sheet and the spacer into the material box, that is, using a manipulator with a negative pressure suction cup to automatically grab the composite gel sheet, using a manipulator with a needle gripper to grab the spacer, and alternately loading the composite gel sheet and the spacer delivered by step S80 into the material box until it is full and enters the material box queue machine; the next step is to stack the loaded material boxes into groups through the lifting and stacking mechanism; the next step is to load the stacked combinations of several material boxes into the same material frame in sequence under the action of the lifting and stacking mechanism until it is full; and then the step is to flip the loaded material frame 90° so that the composite gel sheet is in an upright state in the material frame.
[0177] Optionally, the composite gel fiber sheets or material frames may be transported by a conveying device such as an AGV transfer vehicle.
[0178] Exemplarily, the obtained material frame is transported to a replacement tank by an AGV transfer vehicle, and the solvent replacement is performed for 6 to 12 hours.
[0179] Step S100: drying.
[0180] In some embodiments, the drying is carried out by supercritical drying of carbon dioxide, the supercritical drying temperature is 40 to 65° C., the drying pressure is 8 to 15 MPa, and the drying time is 6 h to 12 h.
[0181] Exemplarily, the material frame replaced in step S90 is placed in a supercritical drying device by an AGV transfer vehicle, and subjected to supercritical drying treatment for 6 to 12 hours to obtain a dried material frame, that is, a dried aerogel composite sheet.
[0182] Optionally, in some embodiments, after the drying step S100, the steps of flipping, sorting and testing the aerogel composite sheet are also included.
[0183] As an example, after drying, the steps further include flipping the aerogel composite sheet by 90°, sorting and inspecting, flipping the obtained material frame to make the material frame outlet horizontal, and making the aerogel composite sheet horizontal in the material frame; removing the material frame in the material frame lifting mechanism; removing the material box in the material box lifting mechanism, and then alternating in sequence, using a manipulator with a negative pressure suction cup to automatically grab the aerogel composite sheet, placing the grabbed aerogel composite sheet on the conveyor belt of the drying equipment for drying, grabbing the spacer with a manipulator with a needle gripper, and placing the grabbed spacer on the spacer queue machine; performing the steps of weight, thickness and visual inspection of the finished product after drying;.
[0184] In summary, the present invention firstly quickly applies glue to the base material coil, adopts sol pressurization, polycondensation material pressurization and pressure continuous feeding rapid mixing technology, under the action of 0.1-7MPa pressure, continuously pumps the sol and the polycondensation agent containing sunscreen and phase change heat storage material into the static mixer, and quickly and continuously uniformly mixes, and forms a catalytic sol of a certain pressure through a coating device, which can quickly immerse in the pores of the base material. And a negative pressure uniform distribution device supporting the base material is adopted, a local negative pressure zone is formed in the base material, which significantly increases the driving force for dipping, promotes the catalytic sol of a certain pressure flowing out of the coating head to further quickly immerse in the base material, greatly promotes the speed and depth of the catalytic sol immersing into the base material, and ensures the fullness of dipping, can achieve the effect of continuous and rapid dipping of the catalytic sol on the base substrate, ensure the consistency of dipping quality and product performance, and obtain a higher yield rate. In addition, since the commonly used dipping pool of the prior art can be omitted, the usage of the sol is also greatly saved, and the production cost is reduced.
[0185] Furthermore, by implementing the gel process under the constraint of double-belt roller pressure, the porosity and pore size in the catalytic sol can be reduced, the fusion degree of the catalytic sol and the matrix material can be improved, the filling amount of aerogel can be increased, and the thermal insulation performance of the aerogel composite sheet can be improved. On the other hand, the surface quality and thickness consistency of the composite gel sheet and the aerogel composite sheet can be greatly improved, the product yield can be significantly improved, the industry's difficulty in controlling the thickness of the aerogel composite sheet can be solved, and the accuracy and consistency of the product thickness and the surface quality and parallelism of the product can be improved.
[0186] The aerogel composite sheet production system provided by the present invention can perform online cutting to a certain length after quick gluing and gel thickness determination under double-belt roller pressure, thereby avoiding the subsequent further cutting process, reducing the generation of scraps, thereby avoiding the waste of aerogel composite materials and saving costs; at the same time, it also avoids the shedding of aerogel powder during the cutting process and avoids dust pollution in the processing environment.
[0187] The present invention arranges and flips the composite gel sheet between slitting and replacement, and after drying, flips and arranges the aerogel composite sheet by 90 degrees, which can increase the number of aerogel composite sheets placed at one time in the replacement and supercritical drying processes, improve the production efficiency of the aerogel composite sheet, and utilize the clamping effect of the spacer on the aerogel composite sheet to ensure that the aerogel composite sheet is not easy to deform during the replacement and drying processes, ensure the thickness consistency, surface quality and parallelism of the aerogel composite sheet during the production process, and ensure a higher yield. The aerogel composite sheet is in an upright state during the replacement and supercritical drying processes, which is consistent with the flow direction of the replacement solvent or supercritical fluid during the replacement and drying processes, which is beneficial to improving the efficiency of the solvent replacing water in the aerogel composite sheet in the material frame and the drying efficiency of the carbon dioxide supercritical fluid extraction solvent, thereby realizing stable and efficient replacement and carbon dioxide supercritical drying of the aerogel composite sheet, ensuring the continuity of the aerogel composite sheet in the post-gel process, and ensuring a higher yield.
[0188] Example 1
[0189] A method for preparing an aerogel composite material comprises the following steps:
[0190] Step S10: preparing sol.
[0191] The preparation of sol specifically includes: mixing tetraethyl orthosilicate, methanol, water and 3% hydrochloric acid aqueous solution, and reacting to obtain sol. The reaction temperature is 40°C and the reaction time is 4 hours. The mass ratio of tetraethyl orthosilicate, methanol, water and 3% hydrochloric acid aqueous solution is 1:1.5:1.8:0.0035.
[0192] Step S20: preparing polycondensation material.
[0193] The preparation of the polycondensation material specifically includes: using a polycondensation material preparation device, according to the ratio requirements, first mixing a 10% ammonia solution with water and stirring for 5 minutes, then adding titanium dioxide and solid paraffin and stirring for 10 minutes to prepare a polycondensation agent mixed liquid containing a sunscreen and a phase change heat storage material.
[0194] Step S30: rapid mixing.
[0195] The prepared sol is pressurized under the first pressure, and the prepared polycondensation material is pumped into the mixing unit under the second pressure to mix, so as to obtain a catalytic sol. The mixing time of the sol and the polycondensation material in the mixing unit is 10 seconds. The sol is pressurized by the first pressurizing pump, and the pressure of the first pressurizing pressure is 2.0 MPa. The polycondensation material is pressurized by the second pressurizing pump, and the pressure of the second pressurizing pressure is 2.0 MPa. The volume ratio of the sol to the polycondensation material is 1.5.
[0196] Step S40, unwinding the rolled felt.
[0197] The base material coil is unwound on the unwinding device.
[0198] Step S50: applying glue.
[0199] The prepared catalytic sol is quickly immersed in the base material. For example, the catalytic sol is immersed in the base material under the pressure formed by the glue coating component to obtain the dipped base material. The pressure of the glue coating component is 1MPa. In the process of immersing the catalytic sol in the base material under the pressure formed by the glue coating component, a negative pressure device is used to form a local negative pressure area in the base material. In the process of immersing the catalytic sol in the base material under the pressure formed by the glue coating component, an ultrasonic vibration device is used to heat the base material and apply ultrasonic vibration.
[0200] Step S60: determining the thickness of the gel.
[0201] The thickness of the matrix material after the dip is determined during the process of the catalyst sol in the matrix material after the dip to gel, so as to obtain a composite gel. For example, on a double belt roller press, gelation is carried out under the pressure constraint formed between the moving upper and lower rollers, and the catalyst sol entering therein is gelled during the process.
[0202] Step S70: Aging.
[0203] The composite gel obtained in step S60 is subjected to microwave aging, wherein the microwave aging temperature is 60° C. and the microwave aging time is 60 min.
[0204] Step S80: cutting.
[0205] The aged continuous composite gel obtained in step S70 is cut into required sizes in both the longitudinal and transverse directions to obtain composite gel sheets.
[0206] Step S90: Replacement.
[0207] The composite gel sheet obtained in step S80 is subjected to solvent replacement; the replacement time is 10 hours.
[0208] Step S100: drying.
[0209] The drying process was carried out by supercritical carbon dioxide drying, the supercritical drying temperature was 60°C, the drying pressure was 14 MPa, and the drying time was 8 h.
[0210] In order to verify that the preparation method of the aerogel composite material provided by the present invention can achieve the effect of high thickness consistency of the aerogel composite sheet, the preparation method provided by the embodiment of the present invention was used for production, and multiple groups of experimental verifications were carried out, as shown in Tables 1 to 4 below.
[0211] It can be seen from the data in Tables 1 to 4 that the thickness difference range of the 2.0 mm glass fiber aerogel composite sheet and the thickness difference range of the 4.0 mm ceramic fiber aerogel composite sheet are within ±0.05, achieving a high consistency in the thickness of the aerogel composite sheet with a thicker substrate.
[0212] Table 1 Thickness test results of 2.0 mm glass fiber aerogel composite sheets obtained after supercritical drying
[0213]
[0214] Table 2 Thermal conductivity test results of 2.0 mm glass fiber aerogel composite sheets obtained after supercritical drying at 25 °C
[0215]
[0216] Table 3 Thickness test results of 4.0 mm ceramic fiber aerogel composite sheet obtained after supercritical drying
[0217]
[0218] Table 4 Thermal conductivity test results of 4.0 mm ceramic fiber aerogel composite sheets obtained after supercritical drying at 25 °C
[0219]
[0220] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0221] The basic principle of the present invention is described above in conjunction with specific embodiments. However, it should be pointed out that the advantages, strengths, effects, etc. mentioned in the present invention are only examples and not limitations, and it cannot be considered that these advantages, strengths, effects, etc. must be possessed by each embodiment of the present invention. In addition, the specific details disclosed above are only for the purpose of illustration and facilitation of understanding, rather than limitation, and the above details do not limit the present invention to being implemented by adopting the above specific details.
[0222] It should be noted that the term "and / or" or " / " used in this document is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. The singular forms of "a", "the" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0223] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0224] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An aerogel composite material, characterized in that: The aerogel composite material comprises: Base material; and an aerogel material on the outer surface of the matrix material and / or immersed in the matrix material; The aerogel material includes silica aerogel, a sunscreen and a phase change heat storage material.
2. The aerogel composite material according to claim 1, characterized in that: The sunscreen includes at least one of titanium dioxide, silicon carbide, zirconium oxide, yttrium oxide, carbon black, potassium titanate whisker, magnesium hydroxide, aluminum hydroxide, vermiculite or calcium carbonate; And / or, the phase change heat storage material includes at least one of an inorganic phase change heat storage material, an organic phase change heat storage material or a composite phase change heat storage material.
3. The aerogel composite material according to claim 1, characterized in that: The mass proportion of the sunscreen in the aerogel material is 30% to 160%; And / or, the mass proportion of the phase change heat storage material in the aerogel material is 0% to 50%.
4. The aerogel composite material according to claim 1, characterized in that: The matrix material includes fiber felt and / or foam material; And / or, the aerogel composite material is a sheet-type aerogel composite material.
5. A method for preparing an aerogel composite material, characterized in that: The following steps are involved: Prepare a sol and a polycondensation material respectively, and pump the sol under a first pressurizing pressure and the polycondensation material under a second pressurizing pressure into a mixing unit for mixing to obtain a catalytic sol; Unwinding the base material coil, and dipping the catalytic sol into the base material under the action of the third pressurizing pressure and / or the pressure formed by the glue coating component to obtain the dipped base material; During the process of the catalytic sol in the impregnated matrix material transforming into gel, the thickness of the impregnated matrix material is measured to obtain a composite gel; The composite gel is subjected to aging, cutting, replacement and drying in sequence to obtain the aerogel composite material.
6. The method for preparing an aerogel composite material according to claim 5, characterized in that: The preparation of the sol specifically comprises: The organic silane compound, alcohol solvent, water and hydrolyzing agent are mixed and reacted to obtain a sol; Optionally, the reaction temperature is 25 to 45° C., and the reaction time is 4 to 6 hours; Optionally, the mass ratio of the organosilane compound, alcohol solvent, water and hydrolyzing agent is (0.8-1.5): (0-2): (0.5-8): (0.001-0.06); Optionally, the organosilane compound includes at least one of ethyl orthosilicate, methyl orthosilicate, butyl orthosilicate, isopropyl orthosilicate or alkyl alkoxysilane, wherein the alkyl alkoxysilane includes at least one of methyltrimethoxysilane, dimethyldimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, vinyltriethoxysilane, propyltrimethoxysilane or propyltriethoxysilane; Optionally, the hydrolyzing agent is an aqueous solution of an acidic compound, and the acidic compound includes at least one of hydrochloric acid, phosphoric acid, sulfuric acid, nitric acid, boric acid, formic acid, acetic acid or citric acid.
7. The method for preparing an aerogel composite material according to claim 5, characterized in that: The preparation of the polycondensation material specifically comprises: The polycondensation agent, the sunscreen and the phase change heat storage material are uniformly mixed to obtain the polycondensation material; Optionally, the alkaline compound is first mixed with water and stirred for 3 to 10 minutes to obtain a polycondensation agent, and then a sunscreen and a phase change heat storage material are added and mixed and stirred for 5 to 30 minutes; Optionally, the mass ratio of the alkaline compound to water is (0.01-0.2):1; Optionally, the mass ratio of the sunscreen agent to the polycondensation agent is (0.1-0.5):1; Optionally, the mass ratio of the phase change heat storage material to the polycondensation agent is (0-0.5):1; Optionally, the alkaline compound includes at least one of sodium hydroxide, potassium hydroxide, ammonia, ammonium fluoride, ammonium bicarbonate, sodium carbonate, sodium bicarbonate, ethanolamine, diethanolamine, methylamine, dimethylamine, ethylamine, diethylamine, propylamine, dipropylamine, isopropanolamine, aniline, o-phenylenediamine, m-phenylenediamine or p-phenylenediamine; Optionally, the sunscreen includes at least one of titanium dioxide, silicon carbide, zirconium oxide, yttrium oxide, carbon black, potassium titanate whiskers, magnesium hydroxide, aluminum hydroxide, vermiculite or calcium carbonate; Optionally, the phase change heat storage material includes at least one of an inorganic phase change heat storage material, an organic phase change heat storage material or a composite phase change heat storage material.
8. The method for preparing an aerogel composite material according to claim 5, characterized in that: The sol and the polycondensation material are mixed in the mixing unit for 5s to 20s; Optionally, the pressure range of the first pressurization pressure is 0.1-7 MPa; Optionally, the second pressurization pressure has a pressure range of 0.1 to 7 MPa; Optionally, the volume ratio of the sol to the condensation material is (0.2-5):
1.
9. The method for preparing an aerogel composite material according to claim 5, characterized in that: In the process of immersing the catalytic sol into the base material under the action of the third pressurizing pressure and / or the pressure formed by the glue coating component, a negative pressure device is used to form a local negative pressure area on the base material; Optionally, during the process of immersing the catalytic sol into the base material under the action of the third pressurizing pressure and / or the pressure formed by the glue coating component, an ultrasonic vibration device is used to heat and apply ultrasonic vibration to the base material containing the catalytic sol.
10. The method for preparing an aerogel composite material according to claim 5, characterized in that: The thickness is determined by respectively arranging a first rolling mechanism and a second rolling mechanism on both side surfaces of the base material after the dipped resin.
11. The method for preparing an aerogel composite material according to any one of claims 5 to 10, characterized in that: The aging is microwave aging, the microwave aging temperature is 60 to 75° C., and the microwave aging time is 20 to 60 minutes; Optionally, the drying is performed by supercritical drying, the temperature of the supercritical drying is 40 to 65° C., the drying pressure is 8 to 15 MPa, and the drying time is 6 to 12 hours.
12. The method for preparing an aerogel composite material according to any one of claims 5 to 10, characterized in that: Between the slitting and replacement, there are also steps of sheet arrangement and flipping; Optionally, after the drying, the method further includes the steps of sheet flipping, sheet sorting and sheet inspection.
Citation Information
Patent Citations
Preparation method of gel felt, equipment for preparing gel felt and aerogel felt
CN114477949A
Gel device for sheet aerogel production
CN213972060U